2018
DOI: 10.13057/biodiv/d190513
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and isozyme banding patterns of Cucurbita moschata at different altitudes

Abstract: Hidayati NR, Suranto, Sajidan. 2018. Morphological characteristics and isozyme banding patterns of Cucurbita moschata at different altitudes. Biodiversitas 19: 1683-1689. Aims of this research were to investigate the morphological character and isozyme banding patterns of Cucurbita moschata plants grown at three different altitudes. Samples in this study consisted of leaf, stem, and flowers. The morphological characters were conducted by direct observation in the field and analyzed descriptively as well as sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Recent studies dealing with peroxidase isozyme had been conducted by Suranto et al (2017), who noted that not only the total number of isozyme bands was useful in distinguishing the difference between the healthy and the virus-infected plants, but this enzyme activity on both samples was also able to compare, especially through their band thickness, between the healthy and the diseased plants. Other interesting results of the above two isozymes were reported by Hidayati et al (2018) dealing with Cucurbita moschata at different altitudes. They note that 10 of peroxidase isozymes and 8 of esterase isozymes were recorded.…”
Section: Peroxidase Isozymementioning
confidence: 55%
See 1 more Smart Citation
“…Recent studies dealing with peroxidase isozyme had been conducted by Suranto et al (2017), who noted that not only the total number of isozyme bands was useful in distinguishing the difference between the healthy and the virus-infected plants, but this enzyme activity on both samples was also able to compare, especially through their band thickness, between the healthy and the diseased plants. Other interesting results of the above two isozymes were reported by Hidayati et al (2018) dealing with Cucurbita moschata at different altitudes. They note that 10 of peroxidase isozymes and 8 of esterase isozymes were recorded.…”
Section: Peroxidase Isozymementioning
confidence: 55%
“…It is considered that these isozymes data were recorded to be one of the most often used in conjunction with group of plant differentiation among taro accession (Smith and Balamarugar (2014) and Kumar et al 2015). Similar studies using the same two enzyme systems were also conducted by Hidayati et al (2018) employing the leaf samples of Cucurbita moschata. They recorded 10 bands of peroxidase isozyme and 8 isozymes banding pattern of esterase.…”
Section: Introductionmentioning
confidence: 78%
“…The floral species analyzed are listed in Table S1 together with their main botanical characteristics and the related references therein [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…Gong et al (2018) reported that changing the environmental conditions could cause plants to adapt both morphologically and physiologically. These adaptation processes have the potential to result in both qualitative and quantitative variations in the plant's morphological characters (Hidayati et al 2018). According to Muthumani et al (2013), altitude influences the degree of light intensity, temperature, rainfall, relative humidity, as well as wind velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Pumpkin has several varieties of usefulness for human beings, not only as a staple food, but also for the diet of people with diabetes millitus (DM). This usefulness is related to the low carbohydrate content and it is easy to set (Suranto et al 2015;Hidayati et al 2018). According to Nagar et al (2018) and Quintana et al (2018), the genotype of pumpkins resulted in their different mineral nutrients, in which the highest percentage of carbohydrate content was detected from the pulps.…”
Section: Introductionmentioning
confidence: 99%